1999
DOI: 10.1520/jfs12028j
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting DNA Mixtures in Structured Populations

Abstract: DNA profiles from multiple-contributor samples are interpreted by comparing the probabilities of the profiles under alternative propositions. The propositions may specify some known contributors to the sample and may also specify a number of unknown contributors. The probability of the alleles carried by the set of people, known or unknown, depends on the allelic frequencies and also upon any relationships among the people. Membership of the same subpopulation implies a relationship from a shared evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 5 publications
0
72
0
Order By: Relevance
“…If we then divide the percentages (81.10 by 18.90) we obtain the paternity index value, 4.29. Evett and Weir [6] show the following is the PI formula for this case, (5) When θ = 0.03 and p 2 = 0.1, this formula gives PI = 4.29 which corresponds to HUGIN's result.…”
Section: Paternity Index Calculationsmentioning
confidence: 91%
See 2 more Smart Citations
“…If we then divide the percentages (81.10 by 18.90) we obtain the paternity index value, 4.29. Evett and Weir [6] show the following is the PI formula for this case, (5) When θ = 0.03 and p 2 = 0.1, this formula gives PI = 4.29 which corresponds to HUGIN's result.…”
Section: Paternity Index Calculationsmentioning
confidence: 91%
“…A body of evidence can be evaluated by calculating a likelihood ratio [5]: (1) where E denotes the evidence, H p and H d denote the plaintiff's and defendant's hypotheses, respectively. In paternity cases, the likelihood ratio is termed the paternity index, or PI.…”
Section: Allelic Dependencies and Paternity Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA Mix v. 3.2 software was used for the statistical analysis to calculate the likelihood ratios (Curran et al, 1999) of the sample mixture with genetic profiles. An ancestry coefficient of 0.01 and minimum frequency of 0.01 was used in a database of allelic frequencies of a Brazilian population (Aguiar et al, 2012) with a confidence interval of 95%.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Based on genetic and statistical justification, Balding and Nichols (1994) showed that, in general, if there are y alleles of AZ observed among n alleles, then the probability that the next allele is an AZ is (4) This formula can also be obtained if a state of evolutionary equilibrium has been established (Wright, 1951;Curran et al, 1999).…”
Section: Dna Mixturementioning
confidence: 99%